13. Epid-based in vivo dosimetry for lung SBRT delivered with multiple breath-hold segmented VMAT. (December 2018) - Cilla, S.; Ianiro, A.; Craus, M.; Viola, P.; Macchia, G.; Morganti, A.G.; Valentini, V.; Deodato, F.
Abstract : Purpose: We evaluated an EPID-based IVD method for the dose verification and the treatment reproducibility of SBRT-VMAT treatments in clinical routine. Methods: 10 patients with lung metastases treated with Elekta VMAT technique were enrolled. All patients were irradiated in 5 consecutive fractions, with total doses of 50 Gy. Set-up was carried out with the Elekta stereotactic body frame. Eight patients were simulated and treated using the Active Breath Coordinator (ABC) system, a spirometer enabling patients to maintain a breath-hold at a predetermined lung volume. Two patients were simulated and treated in free-breathing using an abdominal compressor. IVD was performed using the SOFTDISO software (Best Medical Italy). IVD tests were evaluated by means of (i) ratio R between daily in vivo isocenter dose and planned dose and (ii) γ -analysis between EPID integral portal images in terms of percentage of points with γ -value smaller than one ( γ %) and mean γ -values ( γ mean). Alert criteria of ±5% for R ratio, γ % < 90% and γ mean > 0.67 were chosen. Results: 50 transit EPID images were acquired. For the patients treated with ABC spirometer, the results reported a high level of accuracy in dose delivery with 100% of tests within ± 5%. The γ -analysis showed a γ mean of 0.21 ± 0.10 and a mean γ % equal to 96.9 ± 3.9%. Relevant discrepancies were observed only for the two patients treated without ABC, all described by the γ % tests which dropped below 90% for all the tests. and mainly due to a blurring dose effect due to residual respiratory motion. Conclusions: Our method provided a fast and accurate procedure in clinical routine for verifying delivered dose as well as for detecting errors.